Efektifitas Digital Branding, Peningkatan Engagement Dan Promosi Terhadap Penjualan Produk UKM Melalui Media Sosial: Eksistensi UKM Kelurahan Batu Aji - David Humala Sitorus; Arsyad Sumantika (Prosiding, 2023)
Business ideas are affected not only by markets, companies and competitors, but also by changes. Everyone, even large companies, must recognise this. To maintain the "economic" aspect of society, various studies have been conducted to examine good alternative marketing strategies. This study focuses on small and medium enterprises (SMEs) because SMEs have become part of the creative economy. Therefore, the researcher encourages to examine which digital branding strategies are most widely implemented by SMEs. This study describes how to use strategies to increase engagement and patronage of products, how to make products recognised by the wider community through social media, and how to choose the most effective social media to market products, this study focuses on social media. This study uses a qualitative descriptive method, namely library research through books, journals, and relevant websites. The results of this study show that brand strategy is very important for the development of SMEs and can be more easily implemented for SMEs through digital.